Illness, pain, and health care in early Christianity - Rhee, Helen ca. 20./21. Jh. (William B. Eerdmans Publishing Company, 2022)
"An interdisciplinary study that examines the ways early Christians viewed illness, pain, and health care-and how they were influenced in these matters both by their own tradition and by the culture of the larger ancient Greco-Roman world"--